THE EFFECT OF REPLACING WHEAT FLOUR WITH SESAME AND THYME POWDER ON THE QUALITY ATTRIBUTES OF COOKIES - Eshraq Gehad Khudair (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate replacing wheat flour with sesame flour and thyme-affected laboratory-made Cookies. We tested nine substitution levels and a control. Thyme (1, 3, and 5) % and sesame (15, 30, and 50%) % substituted wheat flour. The proportions of thyme and sesame were, ) 1thyme+15 sesame (%,(3thyme+30sesame)%.Moreover, (5 thyme+50 sesame) The chemical composition analysis of the Cookies treatments showed increases in moisture, protein, fat, and ash for treatment A9 (5% thyme and 50% sesame) compared to the control treatment A10, which had 17.90%, 7.60%, and 11.90%, respectively. Treatment A9 (5% thyme + 50% sesame) had 35.8% unsaturated fatty acids. With sesame and thyme replacement ratios, palmitic, linolenic, and oleic acid percentages increased considerably. Raising the thyme replacement ratio alone did not significantly increase. Similarly, replacing thyme and sesame together raised stearic and linoleic acids, but not individually—analysis of Cookies treatments’ iron and calcium content. Significant changes (P<0.05) occurred between the control and other treatments. Iron and calcium levels were greatest in treatment A9 (5% thyme + 50% sesame), with 342 and 86.42 ppm per 100g. The Gas Chromatography-Mass Spectrometry analysis identified Thymol as the active ingredient in thyme.